Perception of veterinary medicine students on stray dogs and their control strategies in Lima, Peru - Vizquerra B., Micaela (2017)
The aim of this study was to determine the perception of the veterinary medicine (VM) students about the presence of stray dogs and their control strategies in Lima. Peru. For this purpose, a self-application questionnaire was designed with multiplechoice questions with one or more response options. It was anonymously applied to VM students from two universities in Lima, after validation of content by expert judges (Binomial distribution test) and a pilot test to students of VM from a third university to assess the internal consistency (Cronbach’s alpha statistical test). A total of 457 surveys were analyzed. Results showed that 36.5% (167) of the respondents perceived stray dogs on the streets had owner. Respondents felt that the main problems felt by these animals were malnutrition (86.7%) parasitism (62.8%) and accidents (54.9%), and the main problems stray dogs cause were unwanted reproduction (76.1%), zoonoses (47.9%) and breaking of garbage bags (40.7%). Students attribute responsibility to address the problem to district municipalities (86.4%) and the Ministry of Health (60.6%). To control the problem, students considered sterilizations (79.0%), adoptions (70.9%) and neutering (60.8%) as the most viable options.